The Role of Capital Structure as a Mediator of Profitability, Company Size, and Business Risk on Company Value (Study on Exporters Listed on the Indonesia Stock Exchange 2019-2023) - Titi Indah Susilowati; Wisnu Mawardi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Capital structure is an important part of a firm's financial structure as a signal to the market about the firm's management and financial prospects. The optimal capital structure decision can increase the value of the company by increasing investors' perception of the company's stability and growth. This study aims to determine the role of capital structure on profitability, company size, business risk on firm value with capital structure as an intervening variable in companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach and secondary data in the form of financial reports or summaries of annual reports from Exporter companies listed on the IDX in the 2019-2023 time span. The population that is the focus of this research is exporter companies listed on the IDX, with a total of 50 companies with a purposive sampling method, Data analysis was carried out using SEM-PLS version 3.2.9. The research results in this study are Profitability has a positive and significant effect on firm value. company size has a negative and significant effect on firm value. business risk has a positive and insignificant effect on firm value. profitability has a positive and significant effect on firm value. company size has a negative and significant effect on firm value. business risk has a positive and insignificant effect on firm value. capital structure has a negative and significant effect on firm value. Profitability has a negative and significant effect on capital structure. firm size has a positive and insignificant effect on capital structure. business risk has a positive and insignificant effect on capital structure.